2020
DOI: 10.3390/cancers12092651
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Progression of Prostate Cancer: Models for Basic and Preclinical Research

Abstract: We have witnessed noteworthy progress in our understanding of prostate cancer over the past decades. This basic knowledge has been translated into efficient diagnostic and treatment approaches leading to the improvement in patient survival. However, the molecular pathogenesis of prostate cancer appears to be complex, and histological findings often do not provide an accurate assessment of disease aggressiveness and future course. Moreover, we also witness tremendous racial disparity in prostate cancer incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 175 publications
(243 reference statements)
0
24
1
Order By: Relevance
“…We demonstrated that the in vitro response in cells growing in monolayer does not always reflect the situation in more complex systems. The strong differential activity of olaparib in 3D vs. 2D growing cells was particularly intriguing, and was not in agreement with the finding obtained with other cellular systems and other drugs [ 34 , 35 , 36 , 37 , 38 ]. Olaparib, a drug currently under investigation in different solid tumors [ 39 , 40 , 41 , 42 , 43 ], is a potential candidate for MPM due to the reported mutations in the BRCA1-associated protein (BAP-1) gene found in MPM.…”
Section: Discussioncontrasting
confidence: 68%
“…We demonstrated that the in vitro response in cells growing in monolayer does not always reflect the situation in more complex systems. The strong differential activity of olaparib in 3D vs. 2D growing cells was particularly intriguing, and was not in agreement with the finding obtained with other cellular systems and other drugs [ 34 , 35 , 36 , 37 , 38 ]. Olaparib, a drug currently under investigation in different solid tumors [ 39 , 40 , 41 , 42 , 43 ], is a potential candidate for MPM due to the reported mutations in the BRCA1-associated protein (BAP-1) gene found in MPM.…”
Section: Discussioncontrasting
confidence: 68%
“…Given the long doubling times of the LNCaP and VCaP cell populations (42 to 51 h; Figure S1) [34], the effects of the agents of interest (Abi, Enz, metformin, and ARAT + metformin combinations) on cell proliferation become apparent only after the longer incubation times. For instance, compared to controls, the anti-proliferative effects of the above treatments on LNCaP cells are observed at day 3 or beyond after the drug treatments ( Figure S1).…”
Section: Metformin and Arat Agents (Enz Abi) Enhance Cell Death In Pmentioning
confidence: 99%
“…Cholesterol is the essential precursor of steroid synthesis, including androgens [ 41 ]. AR signaling drives PCa and plays an essential role in the development and progression of the disease [ 42 , 43 , 44 , 45 , 46 , 47 ]. As an essential component in cell membranes [ 48 ], and a mediator of cell proliferation and inflammatory pathways [ 41 , 49 ], there are multiple ways cholesterol needs can be exploited to target PCa pathophysiology.…”
Section: Background and Focus Of This Perspectivementioning
confidence: 99%